1987
DOI: 10.3758/bf03197722
|View full text |Cite
|
Sign up to set email alerts
|

Intuition in insight and noninsight problem solving

Abstract: People's metacognitions, both before and during problem solving, may be of importance in motivating and guiding problem-solving behavior. These metacognitions could also be diagnostic for distinguishing among different classes of problems, each perhaps controlled by different cognitive processes. In the present experiments, intuitions on classic insight problems were compared with those on noninsight and algebra problems. The findings were as follows: (1) subjective feeling of knowing predicted performance on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
445
0
9

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 565 publications
(489 citation statements)
references
References 25 publications
20
445
0
9
Order By: Relevance
“…The results reported here provide further behavioural evidence in support of distinctions between insight and non-insight tasks and so add to the differences reported by Metcalfe and Weibe (1987) Furthermore, we found that the pattern of loading of non-insight tasks and insight tasks on individual difference measures of System 2 functions differed in an interpretable way. The role of executive functioning and working memory in non-insight tasks was expected and has been frequently reported.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The results reported here provide further behavioural evidence in support of distinctions between insight and non-insight tasks and so add to the differences reported by Metcalfe and Weibe (1987) Furthermore, we found that the pattern of loading of non-insight tasks and insight tasks on individual difference measures of System 2 functions differed in an interpretable way. The role of executive functioning and working memory in non-insight tasks was expected and has been frequently reported.…”
Section: Discussionsupporting
confidence: 62%
“…Metcalfe and Weibe (1987) contrasted 5 insight and 5 non-insight problems and found that feeling of warmth judgements (i.e. how close participants felt to solution) behaved differently for presumed insight as against non-insight tasks.…”
Section: Previous Approaches Contrasting Insight V Noninsight Tasksmentioning
confidence: 99%
“…(Try this, though don't look yet at the solution below 25 ). There is a certain phenomenology common to the discovery of solutions to insight tasks such as the one above (e.g., Sternberg and Davidson 1995;Metcalfe and Wiebe 1987). For instance, once the participant realises that the lines can go beyond the square that is formed by the nine dots, there is with this (and the discovery of other insight problem solutions) a kind of 'aha' experience.…”
Section: Insight Problem Solving Feeling and Virtuementioning
confidence: 99%
“…For instance, in a study by Janet Metcalfe and David Wiebe (1987), participants completed classic insight problems along with 'non-insight' problems (i.e., such as problems where one must simply apply an algebra rule). In each case, participants recorded 'patternsof-warmth' ratings, which reflect the subjects' feelings of approaching a solution.…”
Section: Insight Problem Solving Feeling and Virtuementioning
confidence: 99%
“…First, although it is generally accepted that both gestalt restructuring and incremental search are involved in problem solving, researchers have had limited success integrating these two approaches (Kaplan & Simon, 1990;MacGregor et al, 2001;Metcalfe & Wiebe, 1987). No suitable theory has been proposed that places both aspects of the process in a common conceptual framework.…”
Section: Group Problem Solvingmentioning
confidence: 99%